The Combined Effects of Per- and Polyfluoroalkyl Substances, Metals, and Behavioral and Social Factors on Depressive Symptoms - Olamide Ogundare; Emmanuel Obeng-Gyasi (Medical Sciences)
Background: This study investigates the combined effects of PFAS metals (PFOA and PFOS), heavy metals (lead, cadmium, and mercury), behavioral factors (smoking and alcohol consumption), and social factors (income and education) on depressive symptoms. Methods: Using cross-sectional data from the National Health and Nutrition Examination Survey (NHANES 2017–2018), blood samples were analyzed to determine the exposure levels of PFOA, PFOS, lead, cadmium, and mercury, and self-reported behavioral and social factors were evaluated in relation to PHQ-9 scores among 181 adults. Results: Education was associated with lower odds of depressive symptoms (OR = 0.68, 95% CI: 0.43–1.07). Although the result was not statistically significant, the estimate suggested a potential protective effect that warranted further investigation. Bayesian Kernel Machine Regression demonstrated that heavy metals collectively had the strongest evidence for influencing depression (group PIP = 0.6508), followed by socioeconomic factors (group PIP = 0.642). Bivariate exposure–response analyses revealed complex interaction patterns whereby exposure effects varied substantially depending on co-exposure contexts. Conclusions: These findings highlight that depressive symptoms are shaped by complex interplays between environmental contaminants, behavior, and social determinants, underscoring the importance of mixture-based approaches in environmental mental health research and the need for integrated interventions addressing both environmental and social factors.